The First Investigation of Microplastics Contamination in Estuarine Located in Puger District, Jember Regency, Indonesia - Selvi Ariyunita; Yeny Dhokhikah; Wachju Subchan (Universitas Negeri Surabaya, 2021)
Microplastics are harmful to the ecosystem and need to solve immediately. Detection of microplastic contamination is the first step to reduce plastics pollution. Estuarine in Puger has a high potential for microplastic pollution related to the multifunction of waters as ports, tourism, fish market, fish processing, and human settlements. However, there are no studies related to microplastic contamination in the area. The objectives of this research were to determine microplastic contamination in the estuarine located in Puger District, Jember Regency, Indonesia. The research results were the first evidence to inform the society and local government about the actual condition of plastic pollution, especially in the aquatic ecosystem. The sampling sites were determined by purposive sampling. Fifty liters of water from each station (with three repetitions) were taken using a 24V water pump and then filtered using stainless steel filter (mesh 5 mm and 0.2 mm). The filtered samples were placed in a sterile bottle sample, stored at 4 ± 20C. Microplastics were counted and categorized according to size, color, and type under a microscope stereo. Microplastic abundance was calculated based on the number of microplastic particles identified per liter of sample water (particle/liter). The result showed that the study area was contaminated by microplastics throughout site sampling, with abundances varying from 0.03 particles/liter to 0.19 particles/liter. The highest microplastic abundance found near the fishery market. The microplastics also vary in size, color, and type. According to characterization, the sources of microplastic contamination come from human-based activities.